2013
DOI: 10.5897/ajmr12.593
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, cultural, pathogenic and molecular studies of Alternaria brassicae infecting cauliflower and mustard in India

Abstract: Dark leaf spot (Alternaria brassicae) is one of the important diseases in crucifers causing serious yield and quality loss in production due to the seed borne nature of the pathogen. Variation in morphology and cultural characteristics among 32 representative Indian geographical isolates of Alternaria brassicae, the causal agent of Alternaria blight of cauliflower (Vegetable) rapeseed-mustard (Oil seed), was studied. All the isolates showed high level of variability in vitro in respect of conidial length, widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
4
4
0
Order By: Relevance
“…As far as colony shape and zonation was concerned, isolates Ab 1, Ab 4 , Ab 7 , Ab 11 and Abl 4 had circular shape with no zonation whereas in Ab 2, Ab 10 , Abl 2 and Abl 5 colony shape was circular with zonation (Table 2). These results are in agreement with earlier workers (Meena et al 2005, Patni et al 2005, Kaur et al 2007, Sharma et al 2013.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As far as colony shape and zonation was concerned, isolates Ab 1, Ab 4 , Ab 7 , Ab 11 and Abl 4 had circular shape with no zonation whereas in Ab 2, Ab 10 , Abl 2 and Abl 5 colony shape was circular with zonation (Table 2). These results are in agreement with earlier workers (Meena et al 2005, Patni et al 2005, Kaur et al 2007, Sharma et al 2013.…”
Section: Resultssupporting
confidence: 94%
“…Variability studies are important to document the changes occurring in the population and individuals as variability in morphological and physiological traits indicate the existence of different pathotypes. Many reports on the existence of variability among different Alternaria species have been reported by earlier workers (Verma et al 2006, Kaur et al 2007, Kumar et al 2008, Goyal et al 2011, Sharma et al 2013, Singh et al 2015. The present study was conducted to find out the variability in Alternaria brassicae and A. brassicicola.…”
Section: Introductionmentioning
confidence: 76%
“…was observed in SIR isolate (1.00) which was statistically similar to DINAb (1.33). These results are in agreements with earlier workers (Sharma et al, 2013;Pramila et al, 2014;Singh et al, 2016;Singh 2018, Singh andSingh, 2018), who observed morphological variability in different geographical isolates within Alternaria isolates. Khan et al (2007) Kumar et al (2014) and Giri (2013).…”
Section: Discussionsupporting
confidence: 94%
“…The colour of colonies varies between light brown to black on PDA. Diversity in colony colour, growth, its margin and topography were noticed among the isolates of A. brassicae by different workers (Sharma et al, 2013, Pramila et al, 2014, Singh et al, 2015, Singh et al, 2016, and Singh and Singh, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic observation revealed variation in the conidia morphology of the pathogen isolates, which is consistent with the findings of Mugao et al [20] where variability of the tomato early blight pathogen in Mwea was reported. Furthermore, the observations on the morphological traits of the conidia are in agreement with other studies where conidia have differed in breadth, length, and beak and have been reported to be straight, slightly curved, muriform or ellipsoid [44][45][46][47][48]. The conidial transverse and longitudinal septa varied ranging from 1 to 6 and from 0 to 2, respectively, which was in tandem with other studies [45,46,47,49].…”
Section: Characterization Of Early Blight Pathogensupporting
confidence: 90%